Chip formation mechanism and machinability of wrought duplex stainless steel alloys - Nomani, J.; Pramanik, Alokesh; Hilditch, T.; Littlefair, G. (Springer, 2015)
This paper investigates the chip formation mechanism and machinability of two-phase materials, such as, wrought duplex stainless steel alloys SAF 2205 and SAF 2507. SEM and optical microscopic details of the frozen cutting zone and chips revealed that the harder austenite phase dissipates in the advancement of the cutting tool, being effectively squeezed out of the softer ferrite phase. Microhardness profiles reveal correlation in hardness from the workpiece material transitioning to the chip. The tool wear (TiAIN + TiN coated solid carbide twist drill) and machining forces were investigated. Tool wear, was dominantly due to the adhesion process which developed from built-up edge formation, is highly detrimental to the flank face. Flute damage was also observed as a major issue in the drilling of duplex alloys leading to premature tool failure. Duplex 2507 shows higher sensitivity to cutting speed during machining and strain hardening at higher velocity and less machinability due to presence of higher percentage of Ni, Mo and Cr.